Proaktywność versus poczucie skuteczności w procesie konstruowania kariery przez młodzież - Myszka-Strychalska , Lucyna (Kultura-Społeczeństwo-Edukacja, 2020)
The contemporary labour market is characterised by broadly understood flexibility which conditions the uncertainty of the professional situation of a person participating therein. One of the factors increasing their chances to have a successful career are not only relevant competences, qualifications and proactive behaviours to the benefit of their own development, but also their trust in their own abilities. In this article it has been attempted to confirm the thesis on the existence of co-dependence between the individual’s proactivity and self-efficacy in the process of developing a professional career. To this end, a review of selected theoretical depictions on both, constructs and results of research explorations specifying mutual relations, was conducted. The observations made have both, theoretical and practical implications that are interesting in cognitive terms. The analysis thereof may prove to be especially important with regard to young people who are preparing to enter the labour market.